Forgiving and Repenting: How to work with that bridge building capacity? (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
After being hurt by others or having committed an error by myself we can become active and restore the damage. When others caused the pain, we can use forgiveness. And for reconciling with myself I can regret or repent. The steps for working with these concepts are presented.
Keywords: Existential analysis (Vienna); coping reactions; forgiveness; regret; repentance; restructuring authenticity